2003
DOI: 10.1074/jbc.m305685200
|View full text |Cite
|
Sign up to set email alerts
|

The Transmembrane Domain Region of Nicastrin Mediates Direct Interactions with APH-1 and the γ-Secretase Complex

Abstract: Nicastrin (NCT) is a type I integral membrane protein that is one of the four essential components of the ␥-secretase complex, a protein assembly that catalyzes the intramembranous cleavage of the amyloid precursor protein and Notch. Other ␥-secretase components include presenilin-1 (PS1), APH-1, and PEN-2, all of which span the membrane multiple times. The mechanism by which NCT associates with the ␥-secretase complex and regulates its activity is unclear. To avoid the misfolding phenotype often associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
63
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 46 publications
12
63
0
Order By: Relevance
“…Interestingly, immature NCT and APH-1aL as well as the low levels of residual mature NCT (because of the incomplete PEN-2 knockdown) remained stable (Fig. 2B), consistent with the observation that these two proteins can independently stabilize each other (13,20,24,25). Taken together, these data demonstrate that PEN-2-⌬C is highly unstable.…”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations
“…Interestingly, immature NCT and APH-1aL as well as the low levels of residual mature NCT (because of the incomplete PEN-2 knockdown) remained stable (Fig. 2B), consistent with the observation that these two proteins can independently stabilize each other (13,20,24,25). Taken together, these data demonstrate that PEN-2-⌬C is highly unstable.…”
Section: Resultssupporting
confidence: 75%
“…This is in contrast to correctly assembled ␥-secretase complex components, which have been shown to be very stable and have a long half-life time (9,17,44,48). The failure of PEN-2-⌬C to stably assemble with PS, NCT, and APH-1 was associated with a marked selective instability of the PS1 NTF and CTF, which also underwent proteasomal degradation, whereas NCT and APH-1 were stable, consistent with previous findings that these proteins can stabilize each other independently (20,24,25). These data suggest that PEN-2 has a dual function as follows: a function in the initiation of PS endoproteolysis as a first maturation step during ␥-secretase complex assembly, and a second function in the stabilization of the PS fragment heterodimer within the ␥-secretase complex that is required for further maturation of the ␥-secretase complex.…”
Section: Pen-2-dependent Stabilization Of Ps Ntf/ctf Heterodimersupporting
confidence: 78%
See 2 more Smart Citations
“…Evidence for selfassociation of APH-1a with itself and with APH-1b was also reported previously [16]. Morais et al demonstrated that NCT and APH-1 were able to interact in vitro in the absence of PS [44]. Our results suggest that all four putative complex components could be detected in the PS complex for embryonic mouse brain after BN/PAGE, and that APH-1 association may be diminished by carbonate wash.…”
Section: Second Dimension Denaturing Electrophoretic Analysis Of Semisupporting
confidence: 69%